Polymers with Intrinsic Microporosity as Solid Ion Conductors for Solid‐State Lithium Batteries - Wang, Xiao‐Xue; Song, Li‐Na; Zheng, Li‐Jun; Guan, De‐Hui; Miao, Cheng‐Lin; Li, Jia‐Xin; Li, Jian‐You; Xu, Ji‐Jing (Angewandte Chemie International Edition, 2023)
Solid‐state electrolytes (SSEs) with high ionic conductivity and superior stability are considered to be a key technology for the safe operation of solid‐state lithium batteries. However, current SSEs are incapable of meeting the requirements for practical solid‐state lithium batteries. Here we report a general strategy for achieving high‐performance SSEs by engineering polymers of intrinsic microporosity (PIMs). Taking advantage of the interconnected ion pathways generated from the ionizable groups, high ionic conductivity (1.06×10−3 S cm−1 at 25 °C) is achieved for the PIMs‐based SSEs. The mechanically strong (50.0 MPa) and non‐flammable SSEs combine the two superiorities of outstanding Li+ conductivity and electrochemical stability, which can restrain the dendrite growth and prevent Li symmetric batteries from short‐circuiting even after more than 2200 h cycling. Benefiting from the rational design of SSEs, PIMs‐based SSEs Li‐metal batteries can achieve good cycling performance and superior feasibility in a series of withstand abuse tests including bending, cutting, and penetration. Moreover, the PIMs‐based SSEs endow high specific capacity (11307 mAh g−1) and long‐term discharge/charge stability (247 cycles) for solid‐state Li−O2 batteries. The PIMs‐based SSEs present a powerful strategy for enabling safe operation of high‐energy solid‐state batteries. Electrolytes based on polymers with intrinsic microporosity (PIMs) are proposed as ideal solid electrolytes for lithium batteries. Benefiting from rational material selection and structure design, solid‐state Li−O2 batteries deliver high discharge specific capacity (11307 mAh g−1) and prolonged cycling life (247 cycles). The solid‐state Li‐metal batteries can operate steadily for over 100 cycles after a series of abuse tests (bending and twisting).